Prototype of Integrated Pier Entrance Gate Access With QR-Code as An Iot-Based Manifest Recording System - Diyasa, I Gede Susrama Mas; Putra, I Nyoman Dita Pahang; Merdana, I Gede Okta Budi; Sampurno, Ilham Ade Widya (Future Science, 2020)
The pier is the place where the ships are being moored at the port. It is also a place for loading and unloading activities and for people or passengers to get on or get off from the ships. There is a need for a digital recording of vehicles or passengers entering the ships to speed up the port administration process. For this reason, in this study, a prototype of a Vehicle and Passenger Recording System (Manifest) at the dock access gate is integrated in an integrated manner based on the Internet of Thing (IoT), which consists of an Android and Web system. This system uses a QR-Code as a ticket that contains manifest data and is read with a QR-Code Reader to be compared with the data stored in the server. If it is appropriate, the dock entrance will be active, and the vehicles or passengers can enter the ships. Whereas if it does not fit, they cannot be open the pier access door. From the test results, the mechanical system can function as expected and can recognize as the entire QR-Code within an optimal distance of 3 cm. All registered users can open the door, as well.